U-Curve Analysis of Cultural Adaptation in IISMA Warwick Students: The Impact of Time Constraints on the Adjustment Process - Benung, Adventius Mayvero; Aldien, Narendra Nizam; Ramadhani, Azlia; Ramadhania, Aisyah Puspita (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This research focuses on the process of cultural adaptation experienced by students who received the IISMA scholarship and studied at Warwick University in the United Kingdom. These students participated in an international exchange program that lasted only one semester, which created unique time constraints compared to longer-term programs. Using the U-Curve theory as a framework, this research applies a qualitative approach by conducting structured interviews with four IISMA Warwick awardees to better understand how students adapt in a short period of time. The findings show that most students went through the typical phases of the U-Curve theory—honeymoon, culture shock, adjustment, and mastery. However, because of the limited duration of their stay, these phases happened more quickly than what is usually expected. Many students entered the adjustment phase much earlier than predicted, although none of them had fully reached the mastery phase. The awareness of having only a short time abroad pushed them to respond more quickly and actively to challenges such as language barriers, academic differences, and social adjustments. This research highlights the need to revise or adapt traditional cultural adjustment models for short-term programs. Since few studies have explored how students adapt under strict time constraints, especially in one-semester programs, this research provides an original contribution. It also emphasizes the importance of creating contextual support systems that match the fast-paced nature of short-term cultural adaptation experiences.